Sexual Health and Sexual Education for Women with Disabilities: Challenges & Opportunities - Leanage, Allison; Burgess, Raquel; Ogrodnik, Michelle; Malik, Peter (McMaster Research Shop, 2018)
Women with disabilities (both physical and intellectual) have a higher risk of experiencing sexual violence due to systemic oppression (the barriers we create as a society and the environment that limits access to services, information, opportunities, experiences etc.). This paper will explore current research about sexual violence experienced by people with disabilities, discuss the gaps in sexual education for this community, and evaluate future needs for more effective and informative education and violence prevention.
Keywords: sexual health; sexual education; disability; women